2019
DOI: 10.4236/oalib.1105141
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Leisure Agriculture on Package Group Tours: A China’s New Tourism Laws Perspective

Abstract: In recent years, China's package group tours have a strong consumption capacity, which is conducive to the integration of various industries. In particular, package group tours in leisure agriculture are different from traditional tourism development and package group tours are developing rapidly. Among them, leisure agriculture in the context of collective tourism is conducive to market demand, and on the other hand, it becomes a new type of agricultural production and tourism and tourism because of the needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The tourism industry is believed to be one of the mainstay sectors of the region to improve people's welfare (Irwan et al, 2021;Pitana and Gayatri, 2005). Concerning agriculture, there is a combined term between tourism and agriculture (Han et al, 2020), namely agrotourism, that introduces related agriculture in tourism packages (Lan and Hung, 2019;Maruti, 2009;Mulyo et al, 2021). Han et al, (2020) found that tourism and agriculture can help to sustain destinations by increasing tourist-stakeholder satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The tourism industry is believed to be one of the mainstay sectors of the region to improve people's welfare (Irwan et al, 2021;Pitana and Gayatri, 2005). Concerning agriculture, there is a combined term between tourism and agriculture (Han et al, 2020), namely agrotourism, that introduces related agriculture in tourism packages (Lan and Hung, 2019;Maruti, 2009;Mulyo et al, 2021). Han et al, (2020) found that tourism and agriculture can help to sustain destinations by increasing tourist-stakeholder satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Since the imple-mentation of the China Tourism Law in 2013, after years of development, Chi-T.-A. Hung et al DOI: 10.4236/oalib.1105287 6Open Access Library Journal na's leisure agriculture has formed many leisure agricultural brands with local characteristics and certain cultural influences[19]. Many related raw materials come from agricultural products, which promote the development of local leisure agriculture[20].First of all, the planning of the creative agriculture complex and the agricul-tural tourism complex, from the perspective of planning content, emphasizes the development of modern agricultural industry, is based on the joint construction of agricultural science and technology and agricultural, industrial chain, promotes the integration and development of the first, second and third generations; It is one of the main ways to focus on the development of ecological civilization; it is to promote the income of farmers in suburban areas and contiguous rural areas, and it is the primary way to strengthen the collective economy.…”
mentioning
confidence: 99%